72.0k views
4 votes
A=(a+b)2h Solve for a. a=2Ah−b a=2A−bh a=2Ah+b a=Ah2−b

User Jtdubs
by
5.5k points

2 Answers

2 votes
A= 2bh/1-2h idk of I’m right or not
User Pnmn
by
6.1k points
2 votes

Answer:

Option a -
a=(2A)/(h)-b

Step-by-step explanation:

Given : Expression
A=(a+b)/(2)* h

To find : Solve for a ?

Solution :

Step 1 - Write the expression,


A=(a+b)/(2)* h

Step 2 - Multiply by 2 both side,


2A=a+b* h

Step 3 - Divide by h both side,


(2A)/(h)=a+b

Step 4 - Subtract by b both side,


(2A)/(h)-b=a

Therefore,
a=(2A)/(h)-b

So, Option a is correct.

User TimothyBuktu
by
5.8k points